PENERAPAN MODEL PEMBELAJARAN TUNTAS UNTUK MENINGKATKAN KETUNTASAN HASIL BELAJAR SISWA PADA MATERI VOLUME KUBUS DAN BALOK DI KELAS V SD NEGERI 137524 TANJUNGBALAI - TIORIM RAJA GUKGUK (LP2MTBM MAKARIOZ, 2018)
This study aims to determine the increase in completeness of student learning outcomes by applying a complete learning model on the volume of cube and beam material in class V 137524 Public Elementary School Tanjungbalai 2016/2017 academic year. This classroom action research takes place in two cycles. The study was conducted in February 2017 until May 2017. The research subjects were all students of class V 137524 Public Elementary School Tanjungbalai 2016/2017 academic year which amounted to 25 students. The results of the study indicate that; 1) student learning outcomes increase by applying the formative learning model I shows an average of 70 with classical completeness of 56% and formative II shows an average of 79 with 88% classical completeness or achieves calcical completeness and a 32% increase. There is an increase in completeness of student learning outcomes; 2) student learning activities increase by applying a complete learning model, attention activity rises from 56.60% to 87.20%, activity notes explanation also rises from 56.60% to 87.80%, activity asks teachers increases from 53, 00% to 87.80%, working on the problem also increased from 64.80% to 90.20%, while the activity of making summaries also increased significantly, from 53.80% to 88.60%.